Preparing to Work with Generation Z - Cecilia Elizabeth Suarez; Valerie McKee (EDIS)
Members of Generation Z, the incoming generation of college graduates and future members of the workforce, will require specific leadership and support to reach their potential and contribute to the needs of the agriculture industry. This 3-page publication describes Generation Z and offers best-known practices for preparing this generation to contribute to Florida’s agriculture and natural resource industries. Written by Celia Elizabeth Suarez and Valerie McKee and published by the UF/IFAS Department of Agricultural Education and Communication, August 2018. https://edis.ifas.ufl.edu/wc311